Development of Canva-Assisted Learning Videos on Matrix Multiplication Material for Grade XI - Dinna Cilvia Asri; Ratu Ilma Indra Putri; Zulkardi Zulkardi (JURNAL PENDIDIKAN MATEMATIKA, 2026)
Abstract. This study aims to develop and assess the feasibility of learning videos, created with the Canva application, for matrix multiplication material for eleventh-grade senior high school students. The study employed a development research method using a development model combined with Tessmer’s formative evaluation, which includes the stages of preliminary, design, and formative evaluation (self-evaluation, expert review, one-to-one, small group, and field test). The research subjects consisted of three expert validators, namely a content expert, a media/design expert, and a language expert, as well as eleventh-grade students involved in the one-to-one test (3 students), small group test (9 students), and field test (36 students). Data collection techniques included needs analysis questionnaires, walkthroughs or expert validation, student response questionnaires, and pretest–posttest assessments. Data analysis was conducted by calculating validity and practicality percentages using a Likert scale, and effectiveness was tested using a paired-samples t-test with a significance level of 0.05. The results indicate that the developed learning video falls into the very valid category based on expert assessments. Practical testing shows that the media is efficient and receives positive responses from students. Effectiveness testing at the field test stage reveals a significant difference between the average pretest and posttest scores, indicating that the Canva-assisted learning video is efficacious in improving students’ learning outcomes in matrix multiplication. Therefore, the developed learning video is declared valid, practical, and effective for use in eleventh-grade senior high school mathematics learning.Keywords: Canva; Matrix Multiplication; Mathematics; Media Development